Cleaner agricultural production in drinking-water source areas for the control of non-point source pollution in China. (1st May 2021) - Wang, Rongjia; Wang, Qingbing; Dong, Linshui; Zhang, Jianfeng
Abstract: With continuous population growth and acceleration of urbanization in China, environmental problems in drinking-water source areas have become increasingly prominent. In some places, domestic wastewater and aquaculture sewage are directly discharged into water bodies without any treatment. Also, large amounts of domestic garbage and aquaculture waste are often randomly stacked, seriously polluting the surrounding groundwater and surface water and deteriorating the water quality. Notably, some agricultural production activities can also cause non-point source pollution, resulting from eutrophication of water bodies. In some instances, these activities can lead to nitrogen losses of 0.7%–83.9% and phosphorus losses of 0.6%–82.8%. In view of this situation, the implementation of cleaner agricultural production is of great significance for protecting the environment in drinking-water source areas and maintaining drinking-water safety. Specific practicable measures include formula fertilization through soil testing, integrated pest management, and water-saving irrigation technology. For the livestock- and poultry-breeding industry, it is necessary for large-scale farms to construct excreta discharge treatment facilities, carry out harmless treatment and resource utilization of organic wastes, establish rural biogas septic tanks, and make use of domestic-sewage and livestock-breeding wastewaters. Also, fixed garbage-dumping sites should be built in rural water-source areas, and a unified garbage-disposal station set up to reduce the pollution discharge of domestic garbage. Moreover, it is crucial to strictly control the development and utilization of hillsides in the middle and upper reaches of the drinking-water source area, as well as strengthen the restoration of vegetation and the construction of soil and water conservation forests in these areas. Highlights: Through agricultural clean production measures can increase economic income. Due to educational background, technology is one of the limiting factors. The source of non-point source pollution varies greatly between regions.